La vulneración del derecho a la salud y reparación integral en mujeres sobrevivientes de trata de personas: reflexiones metodológicas (Tema Central) - Mejía Hernández, María Victoria (2025)
This research aims to analyze the violation of the right to health in women who are victims and survivors of the crime of human trafficking, as well as the mechanisms of comprehensive reparation, through the analysis of a judicial ruling in Ecuador. Human trafficking is considered a serious violation of human rights, as its victims are exploited in various forms, often involving extreme violence—particularly against girls, boys, adolescents, and women. A range of social, political, economic, familial, and interpersonal conditions influence and predispose individuals to become victims of this crime, including social exclusion, lifelong experiences of violence, poverty, unemployment, forced displacement, and political crises, among other factors. The study used secondary sources, including international instruments, and primary data obtained through qualitative methodology and interviews, applying thematic categories for analysis. The results of the research, based on the conviction ruling No. 1028120131612, indicate that while the trafficker was prosecuted, the comprehensive reparation measures required greater involvement from the State to address the full scope of harms suffered before, during, and after the crime by the women affected.